Management Strategy for Quality Improvement of Madrasah-Based Education in North Sulawesi - Nurhayati; J.A.M. Rawis; H.N. Tambingon; Jeffry.S.J. Lengkong (Publisher Cv. Inara, 2021)
This research focuses on the management of madrasa-based education quality improvement strategies in North Sulawesi. The research was conducted at three madrasah, namely Manado State Madrasah Tsanawiyah (MTs Negeri 1 Manado), Bitung State Madrasah Tsanawiyah (MTs Negeri 1 Bitung) and Kotamobagu State Madrasah Tsanawiyah (MTs Negeri 1 Kotamobagu). The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of this study indicate that the Strategic Planning for improving the quality of madrasa-based education at MTs Negeri 1 Manado, MTs Negeri 1 Bitung and MTs Negeri 1 Kotamobagu City is carried out by involving all components of madrasas and stakeholders in an effort to improve the quality of madrasa education while still referring to Islamic values as a characteristic of madrasas. The implementation of the strategy to improve the quality of madrasa-based education is realized by implementing work programs in planning for improving the quality of madrasas such as education and training/training, workshops, seminars, organized by the government, ministries and universities. The impact of implementing strategies to improve the quality of education in madrasas can be seen from a number of indicators such as increased learning outcomes, which can be seen from academic and non-academic achievements achieved by students in various activities, and competitions.